Rho GTPases and regulation of cell migration, polarization and adhesion proteins in wounding assay of human corneal epithelial cells - Gan, Kah Hui (2012)
Corneal epithelial cells are involved in ocular surface diseases involving defective wound healing or persistent epithelial erosions. The small G proteins subfamily of the Ras superfamily is known to play a role in cell motility, polarization and modulation of adhesion proteins. Here we show that various Rho protein members are expressed in cultured primary and immortal corneal epithelial cells. Transfection of cultured human corneal epithelial cells was performed using short interfering RNA and dominant negative plasmids against different members of the Rho protein family. On non-traumatic cell migration assays, siRNAs targeting Cdc42, Rac1 and RhoJ, but not those that silence PAK4, a downstream effector of Cdc42, reduced the rate of ‘wound’ closure. Targeting Cdc42 or RhoJ also significantly reduced the proportion of polarized cells measured by Golgi body orientation. On confocal laser microscopy, after immunofluorescent cell staining, it was observed that targeting Cdc42 or RhoJ by RNA interference did not have a noticeable effect on distribution or co-localization of adhesion proteins – talin and paxillin. This study suggests that Rho proteins influence cell migration through its effect on cell polarization, a critical step in cell movement. Modulation of migration of these cells targeting the Rho proteins has potential therapeutic implications.